Kafka as literature of the absurd - Peters, M (Routledge, 2024)
In this chapter, I show where and how Kafka’s work does, and does not, anticipate that what has come to be known as absurd literature. I survey his three novels and several short stories, including “The Metamorphosis,” through which I explore Kafka’s approach to absurd literary qualities. Kafka’s characters are at odds with their worlds. The absurdity lies in a life lived working to be able to live; in thwarted expectations; in thwarted logic and reason; in thwarted dreams. Like absurd literature, his novels are fragmented, circular, and often lack an ending; like in absurd literature his characters all but completely lack a back story; and like absurd literature his stories are often tragicomic. Nevertheless, Kafka’s specific articulation of the absurd lies not in a world that is meaningless but in different worlds whose meanings not only challenge his characters’ understanding but are also out of reach for them. The absurdity lies in characters who continue to strive to understand, and belong to, worlds that will remain unreasonable and illogical to them.